Parametric Estimation and the Cir Model - Saavedra-Gallardo, E (Universidad Catolica del Norte, 2016)
We study parametric estimation in the Cox-Ingersoll-Ross model and establish the stochastic differential equations for the parameters involved in it. © 2016 Proyecciones Journal of Mathematics.